Samba sem mim : por um elogio do excesso - Yurgel, Caio de Oliveira (2013)
The essay aims to evoke an allegorical discussion regarding contemporary Brazilian literature. By means of two varieties of style situated at opposite ends of the literary spectrum the excessive and the concise , it presents an analysis that postulates a range of Portuguese writers as an indirect way of investigating the disappearance of an epic feeling within the realm of Brazilian literature. Furthermore, it is worth mentioning that the essay does not intend to pitch one style against the other (a futile endeavour, given we are not locked inside a dialectical system that should achieve synthesis out of opposing positions), but to point out some values inherent to an excess-prone literature an excess that values creating a fictional world over the ploy of empty linguistic games.